Women's accounts of help-seeking in early rheumatoid arthritis from symptom onset to diagnosis. (December 2014) - Townsend, Anne; Backman, Catherine L; Adam, Paul; Li, Linda C
Background: As interest in gender and health grows, the notion that women are more likely than men to consult doctors is increasingly undermined as more complex understandings of help seeking and gender emerge. While men's reluctance to seek help is associated with practices of masculinities, there has been less consideration of women's help-seeking practices. Rheumatoid arthritis (RA) is a chronic disease that predominantly affects women and requires prompt treatment but considerable patient-based delays persist along the care pathway. This paper examines women's accounts of help seeking in early RA from symptom onset to diagnosis. Methods: We conducted in-depth interviews with 37 women with RA <12 months in Canada. Analysis was based on a constant comparison, thematic approach informed by narrative analysis. Results: The women's accounts featured masculine practices associated with men's help-seeking. The women presented such behaviours as relational, e.g. rooted in family socialisation and a determination to maintain roles and 'normal' life. Discussion: Our findings raise questions about how far notions of gender operate to differentiate men and women's help seeking and may indicate more similarities than differences. Recognising this has implications for policy and practice initiatives for both men and women.